CANARY Eases Water Quality Event Detection. Issue 4 (1st April 2017) - Hall, John; Panguluri, Sri; Murray, Regan; Burkhardt, Jonathan
Abstract : A free software tool from the US Environmental Protection Agency was put through its paces at a midsize water utility and bolstered the utility's water quality event‐detection capabilities.